Meta-Analysis the Effectiveness of Isometric Relaxation and Laser Therapy in Reducing Myofascial Pain Syndrome on Musculus Upper Trapezius - Alifiya Zulfa Indana; Setyo Sri Rahardjo; Hanung Prasetya (Journal of Epidemiology and Public Health, 2021)
Background: Myofascial pain syndrome upper trapezius is a condition of neck pain caused by excessive muscle loading and can occur due to continuous activities with poor posture and ergonomics. There are many interventions that can be given to treat this MPS, such as Post isometric relaxation and laser therapy. This study aims to analyze the effect of post-isometric relaxation and laser therapy on pain reduction in cases of upper trapezius myofascial pain syndrome.Subjects and Method: This study is a syste